BASING MAIN NUMBER OF USING GRADERS IN SMOOTHING IRRIGATED LAND IN BUKHARA PROVINCE - Kuchkarov, J.J; Olmasov , S.X (Educational Research in Universal Sciences, 2023)
This article provides longitudinal interpretations of water-saving techniques and technologies by establishing the optimal value of the depth, diameter, water consumption, number of holes, distances between them, which is applied to wet irrigation of agricultural plants from under the soil.